CD62L as target receptor for specific gene delivery into less differentiated human T lymphocytes - Kapitza, Laura; Ho, Naphang; Kerzel, Thomas; Frank, Annika M.; Thalheimer, Frederic B.; Jamali, Arezoo; Schaser, Thomas; Buchholz, Christian J.; Hartmann, Jessica (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) expressing T cells are a complex and heterogeneous gene therapy product with variable phenotype composition. A higher proportion of less differentiated CAR T cells is usually associated with improved antitumoral function and persistence. We describe here a novel receptor-targeted lentiviral vector (LV), named 62L-LV, that preferentially transduces less differentiated T cells marked by the L-selectin receptor CD62L, with transduction rates of up to 70% of CD4+ and 50% of CD8+ primary T cells. Remarkably, higher amounts of less differentiated T cells are transduced and preserved upon long-term cultivation using 62L-LV compared to VSV-LV. Interestingly, shed CD62L neither altered binding of 62L-LV particles to T cells nor impacted their transduction. Incubation of two days activated T lymphocytes with 62L-LV or VSV-LV for only 24 hours was sufficient to generate CAR T cells that controlled tumor growth in a leukemia tumor mouse model. The data prove that potent CAR T cells can be generated by short-term ex vivo exposure of primary cells to LVs. As a first vector type that preferentially transduces less differentiated T lymphocytes, 62L-LV has the potential to circumvent cumbersome selection of T cell subtypes and offers substantial shortening of the CAR T cell manufacturing process.